2019
DOI: 10.3390/plants9010021
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Risk of Metal(loid)s in Thelesperma megapotamicum Tea Plant

Abstract: This study reports on the harvesting, ingestion, and contamination of American Indian tea Thelesperma megapotamicum grown on the Navajo Reservation in New Mexico. Uranium (U) and co-metal(loid)s (As, Cd, Cs, Mo, Pb, Se, Th, and V) have contaminated local soil and plants. Tea plants were gathered for analysis near U mining impacted areas. The study collected samples of wild tea plants (n = 14), roots (n = 14), and soil (n = 12) that were analyzed with inductively coupled plasma mass spectrometry. Tea harvesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 63 publications
(100 reference statements)
4
10
1
Order By: Relevance
“…The soil concentrations were greater than the plant roots for all sampled plants: As, Cs, Pb, Mo, and Th ( p < 0.001), V ( p < 0.01), U, Se, and Cd ( p < 0.05). These findings were similar to local and international plant studies examining different species of medicinal plants for metal(loid) content (As, Cd, Cs, Pb, Mo, Se, Th, U, V [ 43 , 48 ], Cd, and Pb [ 50 ] ( Table 3 )). In a regional tea soil study [ 43 , 48 ], there were comparable results for As, Cd, Cs, and V but greater concentrations of Pb, Se, and U; there were smaller concentrations of Mo and Th ( Table 3 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The soil concentrations were greater than the plant roots for all sampled plants: As, Cs, Pb, Mo, and Th ( p < 0.001), V ( p < 0.01), U, Se, and Cd ( p < 0.05). These findings were similar to local and international plant studies examining different species of medicinal plants for metal(loid) content (As, Cd, Cs, Pb, Mo, Se, Th, U, V [ 43 , 48 ], Cd, and Pb [ 50 ] ( Table 3 )). In a regional tea soil study [ 43 , 48 ], there were comparable results for As, Cd, Cs, and V but greater concentrations of Pb, Se, and U; there were smaller concentrations of Mo and Th ( Table 3 ).…”
Section: Resultssupporting
confidence: 87%
“…The purpose of this study was to determine if eight abundant and readily accessible species of plants, a locally harvested resource on Diné lands in northwestern NM, were contaminated with U and other associated metal(loid)s. Food-chain contamination in locally harvested food in the Diné community in NM was reported as a plausible exposure pathway [ 42 ]; harvesting and gathering were found to be common practices [ 43 ]. The current study was undertaken to characterize the use of eight common local medicinal plants and contribute novel metal(loid) uptake data.…”
Section: Introductionmentioning
confidence: 99%
“…[20] On the Navajo Nation, it is reported that 30% of the community consumes unsafe water that is intended for livestock only or has unregulated water sources for drinking purposes. [21] Multiple studies have found elevated levels of metal(loid)s, such as arsenic, cadmium, lead, vanadium, manganese, and uranium on Diné lands, [22][23][24][25][26][27][28] and in human drinking water sources in communities that rely on water for ingestion, cleaning, agriculture, animal husbandry, and cultural needs. [29] Hard rock mining and its' toxicants are only one example, as environmental contamination may occur from other industries (i.e., gas, coal, oil).…”
Section: Watermentioning
confidence: 99%
“…While many of these conditions have been typically attributed to socioeconomic factors (e.g., poverty, smoking status, access to medical care), both researchers and Native American communities have both raised concerns regarding environmental health, especially given how traditional Native American life is closely intertwined with the environment. Causal relationships between environmental contaminants and health disparities are difficult to establish, but what is known is that factors such as pre-existing medical conditions, nutritional intake, and smoking status affect the absorption and excretion of toxins [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies such as those by Lewis et al [3] have underlined the far-reaching scope of environmental contamination in tribal communities, while other studies have examined specific forms of contamination in the form of local plants [17], animals and fish used for food [16], and drinking water/local wells [18], and air quality [19]. Works such as these represent a paradigm shift in environmental health studies among Native American populations, as traditional risk assessments have been criticized for failing to encompass the unique nature of Native American life [20].…”
Section: Introductionmentioning
confidence: 99%